2016
DOI: 10.1891/1946-6560.7.3.226
|View full text |Cite
|
Sign up to set email alerts
|

A Survey of Domestic Violence Perpetrator Programs in the United States and Canada: Findings and Implications for Policy and Intervention

Abstract: A 15-page questionnaire, the North American Domestic Violence Intervention Program Survey, was sent to directors of 3,246 domestic violence perpetrator programs (also known as batterer intervention programs, or BIPs) in the United States and Canada. Respondent contact information was obtained from state Coalitions Against Domestic Violence and from various government agencies (e.g., Attorney General) available on the Internet. Two hundred thirty-eight programs completed and returned the questionnaire, a respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
126
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 120 publications
(130 citation statements)
references
References 37 publications
3
126
0
1
Order By: Relevance
“…Cannon et al (2016) found this model to be the primary treatment approach for 29.1% of programs, and the secondary approach for another 25%. In a European study of 54 BIPs in 19 countries, the majority (70%) indicated that they used cognitive-behavioral principles (Hamilton, Koehler, & Lösel, 2012).…”
Section: Psychotherapeutic and Cognitive-behavioral Therapy Modelmentioning
confidence: 99%
See 4 more Smart Citations
“…Cannon et al (2016) found this model to be the primary treatment approach for 29.1% of programs, and the secondary approach for another 25%. In a European study of 54 BIPs in 19 countries, the majority (70%) indicated that they used cognitive-behavioral principles (Hamilton, Koehler, & Lösel, 2012).…”
Section: Psychotherapeutic and Cognitive-behavioral Therapy Modelmentioning
confidence: 99%
“…Furthermore, perpetrators are 60% less likely to be convicted in mandatory arrest and pro-arrest states in comparison to those that have kept discretionary arrest policies (Hirschel, 2008). Also troubling is the disproportionate arrest and prosecution of men (Shernock & Russell, 2012) and the fact that men account for 83%-90% of individuals enrolled in BIPs (Cannon, Hamel, Buttell, & Ferreira, 2016;Price & Rosenbaum, 2009), a percentage that does not reflect prevalence rates of partner violence in the general population.…”
Section: Policies On Intimate Partner Violence Interventionmentioning
confidence: 99%
See 3 more Smart Citations